2017
DOI: 10.1007/978-3-319-69535-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressants and Male Reproduction

Abstract: Prolonged use of immunosuppressant medications is occasionally seen in infertile men with chronic inflammatory conditions; autoimmune disorders; or an organ or hematopoietic stem cell transplant. Chronic inflammation impacts negatively on male reproductive endpoints, so immunosuppressant therapy can produce improvements. Corticosteroids have been used to treat antisperm antibodies and even as an empirical treatment for male infertility in general. Trials of these methods have provided mixed results on semen qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 227 publications
1
16
0
2
Order By: Relevance
“…Because of the scope of our systematic review, studies that reported the effect of corticosteroids on the male reproductive health of healthy controls were excluded. A review on this topic can be found elsewhere ( Drobnis and Nangia, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the scope of our systematic review, studies that reported the effect of corticosteroids on the male reproductive health of healthy controls were excluded. A review on this topic can be found elsewhere ( Drobnis and Nangia, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported mixed results and overall the risks associated with glucocorticoid therapy outweighed the benefits. In-depth information can be found elsewhere ( Drobnis and Nangia, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone, a glucocorticosteroid drug, reduced the mortality rate by one-third in mechanically ventilated patients and by one-fifth for those receiving oxygen without ventilation [ 26 ]. Notably, dexamethasone has been shown to lower testosterone synthesis in animal models [ 35 , 36 ] and human patients [ 36 ]. Lower androgen levels might be a contributor to dexamethasone observed beneficial effects; however, these preliminary results should be interpreted with caution.…”
Section: Androgen Suppression Targeted Treatment For Covid-19mentioning
confidence: 99%
“…The mechanisms of cyclosporine‐induced testicular toxicity include increased release of reactive oxygen species (ROS), increased formation of the proinflammatory cytokines and induction of apoptosis in the spermatogenic cells. These effects may lead to serious toxic events in the gonads which may significantly affect male fertility 4 …”
Section: Introductionmentioning
confidence: 99%